2020
DOI: 10.1007/s42452-020-2657-8
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of tensile, hardness and wear properties of aluminium metal matrix composite through stir casting process

Abstract: Among several methods to fabricate Aluminium metal matrix composites, stir-casting technique is used for large-scale production due to its being less expensive. This research is concerned with the fabrication of Aluminium composites with SiC and Jute Ash Particles, for sake of producing a cost-effective composite with enhanced properties. Wear behaviour was studied using pin on disc tribometer and it was found that wear resistance increases with-addition of reinforcement particles. Fabricated composite samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Recent investigations have revealed that a variety of natural fiber products can be used in advanced engineering applications. Coyal et al fabricated cost-effective AMMCs with SiC and jute ash particles with enhanced properties via stir casting routes [144]. The wear behavior was investigated using a pin-on-disc tribometer, and it was discovered that adding reinforcement particles increases wear resistance.…”
Section: Tribological Studies Of Ammcsmentioning
confidence: 99%
“…Recent investigations have revealed that a variety of natural fiber products can be used in advanced engineering applications. Coyal et al fabricated cost-effective AMMCs with SiC and jute ash particles with enhanced properties via stir casting routes [144]. The wear behavior was investigated using a pin-on-disc tribometer, and it was discovered that adding reinforcement particles increases wear resistance.…”
Section: Tribological Studies Of Ammcsmentioning
confidence: 99%
“…AA6061 was used as the base metal following its excellent welding characteristics and strength that it possesses compared to the high strength aluminium and copper alloys (Coyal et al, 2020). Apart from this, it is chosen due to its easy market availability, wide applications and economical efficiency.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…The matrix is brought to a semi-liquid state, and the reinforcement is injected in the presence of argon gas. 25 After preheating TiB 2 at 250°C for 2 h, the reinforcement was transferred into liquid melt slowly. The mixture is stirred for 15 min at 350 rpm using a titanium stirrer for uniform dispersions.…”
Section: Metal Matrix Composite Fabrication Techniquesmentioning
confidence: 99%